Analytical method for determining axial-flux permanent-magnet machine sensitivity to design variables - Mahmoudi, A.; Rahim, N.A.; Hew, W.P. (Praise Worthy Prize, 2010)
This paper presents an analytical approach to determining sensitivity of a slotted axial-flux permanent-magnet machine to its design variables The method is modeled on a simple nonlinear magnetic analysis of an equivalent magnetic circuit with a saturation-possible magnetic-reluctance core in a slotted axial-flux permanent-magnet machine It calculates flux distribution and torque characteristic in various operating conditions Its accuracy and validity are verified by results that match those of a Finite Element Analysis model The method is as accurate as FEA but betters FEA with its shorter computation time making it the better alternative in initial estimations and in expediting design optimization of electrical machines Design parameters for maximum output torque and efficiency iteratively adjusted through multi-objective optimal design are selected via sensitivity analysis of the proposed magnetic circuit Simulation results show AFPM machine efficiency to be affected the most by its diameter, followed by magnet fraction and the least by back-iron thickness Copyright (C) 2010 Praise Worthy Prize S r l. - All rights reserved.